Service Time-Based Region Division in OVSF-Based Wireless Networks with Adaptive LTE-M Network for Machine to Machine Communications - Vipin Balyan; Davinder S. Saini; Bhasker Gupta (Journal of Electrical and Computer Engineering)
The 3GPP standards have presented the LTE-M as one of the main technologies to provide services to Internet of Things (IoT). The IoT applications are usually short-lived applications like smart sensing, surveillance systems for home or businesses, and data uploading applications like metering. In this paper, the proposed architecture of the base station has a LTE interface which assigns resource blocks (RBs) and another 3G interface which is equipped with orthogonal variable spreading factor (OVSF) codes. The IoT devices deployed ubiquitously leads to massive machine type communication, which leads to burst traffic on current cellular services. The IoT devices when assigned large resources will reduce the radio efficiency. The work in this paper assigns OVSF codes available on 3G interface to the IoT devices. The LTE resources are used for IoT devices in case of emergency or when resources of 3G interface are 100% utilized. This will solve the problem of both small data transfer and connectivity requirement of IoT devices. The IoT applications are event-driven and time-bound also, and the resources are also reserved for these applications in the proposed work. The simulations and results show that proposed work increases both network efficiency and capacity.